Great expectations: A multisite, randomized controlled open‐label trial of a novel patient expectations communication tool - Jennifer Chapman; Michael Wakely; Kelsey Leonard; Elizabeth Piwowarski; Martin P. Wegman (Journal of the American College of Emergency Physicians Open)
Abstract Objectives In emergency medicine (EM), discerning patient expectations to inform patient‐centered care poses unique challenges. We devised a novel questionnaire to facilitate clinicians’ understanding of patients’ expectations for their visit. Methods We conducted a multisite, randomized controlled trial. A brief questionnaire soliciting patient expectations was developed through feedback from clinicians and patients. At the beginning of their visit, the intervention group patients completed the questionnaire and provided it to their treating clinician. The control group patients received standard care. Participants in both groups completed a survey at time of disposition assessing five satisfaction domains. The primary ordinal logistic regression analysis modeled the extent to which the intervention led to patient‐reported improvement in clinician understanding of expectations with adjustment for demographic factors and site. Results Among the 308 participants, 141 intervention and 123 control exit surveys were collected. In the primary analysis, the intervention group had 2.1 times greater odds of strongly agreeing that their clinician understood their expectations (odds ratio: 2.1, 95% confidence interval: 1.2, 3.7, p‐value: 0.01), roughly equivalent to a net number needed to treat of 11 for one more improved satisfaction rating. Although the secondary outcome results were not significantly different between groups, all results tended toward the intervention group having more favorable answers. Conclusions While more patients reported that their expectations were addressed when the novel tool was used, no significant difference was found for conventional satisfaction measures. Future studies may examine whether a tool to elicit patient expectations can lead to other improved outcomes.